Five days exposure to high dietary fat intake has no impact on the performance of a preloaded 5km treadmill based time trial in endurance-trained women. - Fletcher, G.; Glover, E. L.; Thompson, J. L.; Wallis, G. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Manipulating the dietary intake of carbohydrate and fat results in differences in the circulating hormonal and metabolic milieu alongside differences in the myocellular substrate storage profile. These divergent profiles can dramatically impact substrate utilisation during exercise, potentially impacting endurance performance.